Taste and Food Preferences of the Hungarian Roma Population - Judit Diószegi; Péter Pikó; Zsigmond Kósa; János Sándor; Erand Llanaj; Erand Llanaj; Róza Ádány; Róza Ádány; Róza Ádány (Frontiers Media S.A., 2020)
Background: In Central, Eastern, and Southern Europe, the Roma population is the largest and the most vulnerable and disadvantaged minority. Behind their unfavorable health status, harmful health behaviors, such as unhealthy diet is also supposed to exist.Methods: In the framework of a complex health study, individuals from the Hungarian general (n = 410) and Roma populations (n = 387) were randomly selected. In the survey portion of the study, sweet, fat, salty, and bitter taste preferences were ascertained by question items measuring taste and food preferences. Preference for sweet vs. salty foods was also analyzed. Questions from the Hungarian version of the European Health Interview Survey were included, to characterize fruit and vegetable consumption and to determine the quantity of sugars added to consumed foods and beverages and the frequency of salting without tasting the food. Data were analyzed using STATA 9.0 statistical software.Results: Roma reported significantly less frequent consumption of fresh fruits (OR = 1.70, 95% CI: 1.22-2.35, p = 0.002) and vegetables (OR = 1.74, 95% CI: 1.25-2.41, p = 0.001) than the Hungarian subjects. Representatives of the Hungarian Roma population reported adding higher quantities of sugars to consumed foods and beverages (OR = 1.68, 95% CI: 1.10-2.56, p = 0.016) and preferred sweet snacks vs. salty ones (OR = 0.53 for salty snacks, 95% CI: 0.37-0.78, p = 0.001) and had higher preferences for sweet foods (OR = 1.51, 95% CI: 1.08-2.11, p = 0.015). They salted their food without tasting it more often (OR = 2.18, 95% CI: 1.64-2.88, p < 0.001). They had lower preferences for bitter tasting raw kohlrabi (OR = 0.56, 95% CI: 0.41-0.80, p = 0.001), grapefruit (OR = 0.47, 95% CI: 0.34-0.64, p < 0.001), black coffee (OR = 0.50, 95% CI: 0.34-0.73, p < 0.001), and dark chocolate (OR = 0.63, 95% CI: 0.46-0.84, p = 0.006). No significant results in terms of ethnicity were found on for fatty and salty food preference and other bitter-tasting vegetables.Conclusions: Roma diet may be linked to taste preferences predisposing to unhealthy eating habits. This assumption needs further studies on their dietary behavior. In order to design potentially effective intervention programs targeting Roma populations, it is essential to identify individual, environmental, social, cultural, and behavioral factors and as well as their complex interplay that may affect dietary intake and behaviors.